IMPLEMENTASI STRATEGI KOMUNIKASI PEMBELAJARAN DAN KEPEMIMPINAN PEMBELAJARAN SEBAGAI UPAYA MENCIPTAKAN PEMBELAJARAN YANG BERKUALITAS - ., Suyahman (PKn Progresif, 2016)
This study aimed to describe the effort to create quality learning through the implementation of communication strategies of learning and instructional leadership.This study was descriptive qualitative research. Methods of data collection used interview, observation and documentation. Data analysis techniques used interactive analysis techniques, consists of three steps: data reduction, presentation of data, drawing conclusionsThe results showed that the implementation of the communication strategy is multi learning that is supported by the leadership of learning filled with concern for the learning process can help to promote quality learning. Implementation of communication strategies in learning between teachers and students who are humanist, it can clarify the learning process, as well as thought leadership that provide infrastructure support learning, providing opportunities abgi teachers to improve professionalism, creating a learning environment conducive,, as well as the establishment of a harmonious interaction , aligned and integrated between the leadership of learning with the teacher, and the students will be able to support the creation of quality learning.The conclusion is that the implementation of appropriate learning strategies and supported by the leadership of good learning, it can help create quality learning.